(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2019)
This article describes the process of transformation of political positions between right and left of Colombian voters from 1974 to the present. In this historical course, it is possible to establish three stages of the Colombian legal left: 1) between 1974 and 1991; 2) between 1991 and 2003 and 3) from 2003 to the present. The article shows statistically the decrease of voters of the traditional right, the increase of the vote for the extreme right until the increase of the vote for the moderate left, without considering the existence of an ideological change of the electorate. It is established here, contrary to the theory of Rosario Queirolo for other Latin American countries, that Colombia does not show a "bimodal" ideological distribution, but rather a path dependence according to which right-wing ideology has prevailed up to the present among the voters, which only begins to be broken by the electoral presence of an "untainted" leader.